Association of lifelong exposure to cognitive reserve-enhancing factors with dementia risk: A community-based cohort study - Wang, Hui-Xin (PLoS Med, 2017)
BACKGROUND: Variation in the clinical manifestation of dementia has been associated with differences in cognitive reserve, although less is known about the cumulative effects of exposure to cognitive reserve factors over the life course. We examined the association of cognitive reserve-related factors over the lifespan with the risk of dementia in a community-based cohort of older adults. METHODS AND FINDINGS: Information on early-life education, socioeconomic status, work complexity at age 20, midlife occupation attainment, and late-life leisure activities was collected in a cohort of dementia-free community dwellers aged 75+ y residing in the Kungsholmen district of Stockholm, Sweden, in 1987–1989. The cohort was followed up to 9 y (until 1996) to detect incident dementia cases. To exclude preclinical phases of disease, participants who developed dementia at the first follow-up examination 3 y after the baseline were excluded (n = 602 after exclusions). Structural equation modelling was used to generate latent factors of cognitive reserve from three periods over the life course: early (before 20 y), adulthood (around 30–55 y), and late life (75 y and older). The correlation between early- and adult-life latent factors was strong (γ = 0.9), whereas early–late (γ = 0.27) and adult–late (γ = 0.16) latent factor correlations were weak. One hundred forty-eight participants developed dementia during follow-up, and 454 remained dementia-free. The relative risk (RR) of dementia was estimated using Cox models with life-course cognitive reserve-enhancing factors modelled separately and simultaneously to assess direct and indirect effects. The analysis was repeated among carriers and noncarriers of the apolipoprotein E (APOE) ε4 allele. A reduced risk of dementia was associated with early- (RR 0.57; 95% CI 0.36–0.90), adult- (RR 0.60; 95% CI 0.42–0.87), and late-life (RR 0.52; 95% CI 0.37–0.73) reserve-enhancing latent factors in separate multivariable Cox models. In a mutually adjusted model, which may have been imprecisely estimated because of strong correlation between early- and adult-life factors, the late-life factor preserved its association (RR 0.65; 95% CI 0.45–0.94), whereas the effect of midlife (RR 0.73; 95% CI 0.50–1.06) and early-life factors (RR 0.76; 95% CI 0.47–1.23) on the risk of dementia was attenuated. The risk declined progressively with cumulative exposure to reserve-enhancing latent factors, and having high scores on cognitive reserve-enhancing composite factors in all three periods over the life course was associated with the lowest risk of dementia (RR 0.40; 95% CI 0.20–0.81). Similar associations were detected among APOE ε4 allele carriers and noncarriers. Limitations include measurement error and nonresponse, with both biases likely favouring the null. Strong correlation between early- and adult-life latent factors may have led to a loss in precision when estimating mutually adjusted effects of all periods. CONCLUSIONS: In this study, cumulative exposure to reserve-enhancing factors over the lifespan was associated with reduced risk of dementia in late life, even among individuals with genetic predisposition.